(untitled) (Iraqi Journal of Medical Sciences, 2017)
Background: Obstructive jaundice poses diagnostic and therapeutic challenges to practicing physician gastroenterologist and general surgeons. Objective: To highlight the etiological spectrum, treatment outcome of obstructive jaundice endoscopically by Endoscopic Retrograde Cholangiopancreaticography (ERCP). Methods: It is a cross sectional case series study included 140 patients who presented with obstructive jaundice and dilated biliary system. They managed at Gastroenterology and Hepatology Center in Al-Imamein Al-kadhimein Medical City, Baghdad, Iraq from April 2012 to April 2014. All the patients were offered abdominal sonagraphy (U/S), magnetic resonance cholangiopancreaticography (MRCP) and upper endoscopy, as well as other laboratory work up, in order to prepare them for either palliative or curative treatment by the ERCP. Both success rate and complications were reported. Results: Common bile duct (CBD) stones were confirmed in 100 patients (71.4%) (56 female and 44 male) while pancreatic-biliary tumors found in 25 patient (17.8%) (15 male and 10 female) as pancreatic tumor in 11 patients, periampulary and ampulary tumor in 5 patients and cholangiocarcinoma in 4 patients while the rest due to metastasis. Benign causes as biliary fibrosis was seen in (10.8%). The success rate of ERCP treatment was 87.2%, but complications represented 6.4%. All of them were mild and reported within 24 hours. Conclusion: CBD stones are the predominant cause of benign cause of surgical obstructive jaundice, while the carcinoma of head of pancreas is the commonest concerning malignant causes. ERCP is very safe and effective procedure in the management. Keywords: CBD stone, Obstructive jaundice, ERCP, gallstone. DOI: 10.22578/IJMS.14.4.9